KAJIAN HUKUM TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DARI ASPEK KRIMINOLOGI - Sianturi, Benny Eliezer; Simanjuntak, Immanuel; Saragih, Wira Natanael; Aritonang, Zico Ricardo (The Juris, 2024)
Criminal law regulates patterns of human behavior and/or legal entities, in this case in the writing, namely the legal study of perpetrators of narcotics crimes from a criminological aspect. In this study, the author applies a research method that tends to be normative juridical, which is seen not only from the regulatory aspect but also from the study of decisions. Thus, it can provide benefits to the relationship between perpetrators of narcotics crimes and criminology. That in this case the author explains what causes perpetrators to commit narcotics crimes from a criminological aspect (study of decision 1248/pid.sus/2023/PN/Mdn), the author also explains how the role of law enforcement against perpetrators of narcotics crimes from a criminological aspect of the Decision study: 1248/pid.sus/2023/PN/Mdn. Thus, it can be concluded that the causes of perpetrators of narcotics crimes when viewed from a criminological perspective, the cause of the occurrence is mostly due to environmental or community factors, family, personality, and even economic factors. And if seen from the role of law enforcement against perpetrators of narcotics crimes from the criminology aspect, it has actually been running well, but in this case, optimal cooperation is needed in order to reduce narcotics crimes. So that it is not only the role of law enforcement but also all levels of elements, both society, to eradicate narcotics.